Analyzing Indicators of the Results of Applying Forecasting Methods for Production Plans: A Case Study at the Diyala State Company for Electrical Industries - Ismael, Emad Khaleel (Mediterranean Journal of Social Sciences, 2021)
Economic organizations operate in a dynamic environment, which necessitates the use of quantitative techniques to make their decisions. Here, the role of forecasting production plans emerges. So, this study aims to analysis of the results of applying forecasting methods to production plans for the past years, in the Diyala State Company for Electrical Industries. The Diyala State Company for Electrical Industries was chosen as a field of research for its role in providing distinguished products as well as the development and growth of its products and quality, and because it produces many products, and the study period was limited to ten years, from 2010 to 2019. This study used the descriptive approach in the theoretical side of the study, on the practical side, the current study used the statistical application (SPSS), and some other statistical means to process and analyze what was collected from data related to the company, the research sample, from its official website. The research concluded that flooding the Iraqi market with alternative imported products for the products of the Electrical Industries Company led to the cessation of production of some of the company's products, as a result, its resources were not invested efficiently and production costs were high. The current study suggested to the Ministry of Electricity to buy the company's products, as these products have a good quality comparing with the foreign ones. Â  Received: 10 June 2021 / Accepted: 12 August 2021 / Published: 5 September 2021